Iron oxide-doped niosomes as drug carriers for magnetically targeted drug delivery - Juneja R (Dove Medical Press, 2018)
Ridhima Juneja, Indrajit Roy Department of Chemistry, University of Delhi, New Delhi, Delhi, India Abstract: Magnetism has wide applications in various fields, such as diagnostics, drug targeting, molecular biology, cell isolation, cell purification, hyperthermia, and radioimmunoassay. In this study, we synthesized niosomes doped with iron oxide nanoparticles and a fluorophore for potential applications in magnetically targeted drug delivery. Release kinetics of the fluorophore and cytotoxicity were assessed. The results demonstrate that niosomes doped with iron oxide nanoparticles can serve as proficient and effective drug carriers in magnetically targeted drug delivery. Keywords: iron oxide nanoparticles, niosomes, fluorophores, drug carriers, magnetically targeted delivery